Effects of Bile Acids on Growth Performance, Hepatopancreatic Antioxidant Capacity, Intestinal Immune-Related Gene Expression, and Gut Microbiota of Penaeus vannamei - Yun Zhao; Duanduan Chen; Hui Wang (Animals)
This study aimed to examine the impact of varying concentrations of bile acids (BA) added to the feed on several aspects of Penaeus vannamei. The purity of BA was 25.29%, and its main components were 5.74% chenodeoxycholic acid, 6.27% allocholic acid, 3.20% cholic acid, 5.79% hyodeoxycholic acid, and 2.31% hyocholic acid. The experiment was designed with four groups: CT, BA1, BA2, and BA3, where BA were added to the shrimp basal diet at concentrations of 0.0 mg/kg, 0.1 mg/kg, 1.0 mg/kg, and 10.0 mg/kg, respectively. After 60 days of farming P. vannamei (initial body weight: 1.21 ± 0.05 g), the results showed that BA supplementation significantly improved growth performance, and BA2 group was the most significant, which increased the final weight (FBW) by 18.6%, weight gain rate (WGR) by 19.5%, and survival rate (SR) by 5.8% compared with the CT group (p < 0.05). Additionally, the activities of trypsin and lipase in gut tissue were significantly increased (p < 0.05). Furthermore, BA supplementation increased the activity of antioxidant-related enzymes in the hepatopancreas and enhanced the mRNA expression levels of gut-associated immune genes. In addition, the supplementation of 0.1 mg/kg BA significantly altered the gut microbial composition, reducing the proportion of harmful Proteobacteria while enhancing the relative abundance of beneficial microorganisms such as Firmicutes and Bacteroides. In conclusion, 1.0 mg/kg and 10.0 mg/kg BA supplementation significantly improved the growth performance, digestive capacity, and antioxidant capacity of shrimp, among which 1.0 mg/kg supplementation had the most significant effect and improved the intestinal microbial composition of shrimp.